Unintended Consequences of China's New Labor Contract Law on Unemployment and Welfare Loss of the Workers - Randall Akee; Liqiu Zhao; Zhong Zhao (Global Labor Organization (GLO), 2018)
China's new Labor Contract Law, which intended to strengthen the labor protection for workers, went into effect on January 1, 2008. The law stipulated that the maximum cumulative duration of successive fixed-term (temporary) labor contracts is 10 years, and employees working for the same employer for more than 10 consecutive years are able to secure an open-ended (permanent) labor contract under the new law, which is highly desirable to employees. However, in order to circumvent the new Labor Contract Law, some employers may have dismissed workers, after the passage of the new law, who had worked in the same firm for more than 10 years. Using data from the 2008 China General Social Survey, we find strong evidence that firms did in fact dismiss their formal-contract employees who have been employed for more than 10 years. Additionally, using a regression discontinuity design based on this exogenous change in unemployment status for this particular group of workers, we show that the dismissed workers suffered significant welfare loss in terms of happiness. Our results are robust to various specifications and placebo tests.
Keywords: J41; J64; I31; 330; Labor Contract Law; Unemployment; Happiness; Regression Discontinuity Design; China